Essays on the doctrinal study of law - Aarnio, Aulis; SpringerLink (Online service). (New York Springer, 2011)
This book is a summary of the author's 40 years of research in the fields of civil law and the philosophy of law. The main focus is on the two main tasks in the doctrinal study of law: the interpretation and systematisation of legal norms. In this regard, Professor Aarnio deals with the theory of argumentation as well as with its foundations - i.e., with the ontology, epistemology and methodology of legal thinking - and develops the ideas that were first presented in The Rational as Reasonable (Kluwer 1987) in all of these dimensions. The work includes an updated discussion on the writings of Robert Alexy, Jûrgen Habermas, Ronald Dworkin and Alf Ross. A focal point of view concerns the distinction between positivism and non-positivism, in which the core of the criticism focuses on Scandinavian realism
Foreword Part I: Introduction Chapter 1. The Roman Heritage Chapter 2. Bonus Theoreticus, Malus Practicus Chapter 3.What is the Doctrinal Study of Law? Part II: The Foundations of Legal Thinking Chapter 4. Lawyer´s Dilemma Chapter 5. On Language-Games Chapter 6. The Foundations of Knowledge Chapter 7. On the Ontology of Law Chapter 8. A Moral Point of View Chapter 9. The Three Notions of Liberty Part III: Between Realism and Idealism Chapter 10. What is Science? Chapter 11. Legal Realism Reinterpreted Chapter 12. Outlines of the New Rhetoric Chapter 13. Scientific Inference - An Example Part IV: On the Doctrinal Study of Law Chapter 14. From the Constitutional State to the Welfare State Chapter 15. Two Types of Norms Chapter 16. The Formal Validity, Efficacy and Acceptability of Norms Chapter 17. The Procedure of Legal Reasoning Chapter18. The Sources of Law Chapter 19. One Right Answer Chapter 20. On the Systematisation Chapter 21. Change or Development? Bibliography Index
Includes bibliographical references and indexes
Electronic reproduction
Keywords: Ecclesiastical law